Generation of higher-order orbital angular momentum modes and (de)multiplexing based on double-trench SOI waveguide. Issue 2 (19th January 2022) - Bai, Xiuli; Chen, Heming; Cao, Hengying
Abstract : An ultracompact device, designed with two air-etched trenches embedded in two opposite corners of a silicon bus waveguide, for generation and (de)multiplexing optical orbital angular momentum (OAM) modes is proposed. The double-trench waveguide can generate OAM±1 and OAM±2 modes when the phase difference of two rotated orthogonal LP-like modes is equal to π/2 (or 3π/2). The operating principle and mode purity of the generated OAM modes are theoretically and systematically investigated. The simulation results show that the average purities of OAM±1 modes exceed 90%, and that of OAM±2 modes is greater than 80% over a wide wavelength range of 1.4–1.625 µm. Furthermore, an on-chip five-OAM-mode (de)multiplexer (OAM0, OAM±1, OAM±2 ) with a compact footprint of <200×4×4 µm 3 is designed, whose main mode crosstalk is less than −20 dB. The presented OAM mode generator and (de)multiplexer are promising for applications like optical communications and quantum information processing.